تصميم ألعاب لغوية لتعليم اللغة العربية من خلال الكلمات الإندونيسية ذات أصل قرآني - Yusri sofa mubarok; Hadil ismail (Rayah Al-Islam, 2020)
This study aims to provide the teacher and learner knowledge of the Arabic language to speakers of other languages ​​through one of the teaching methods, which are language games from Indonesian words of Quranic origin from Surat Al-Fatihah to Surat Al-Nisaa, To achieve this goal, the researcher used in his research the descriptive analytical approach that paved the way for the researcher to analyze the Indonesian vocabulary of Qur'anic origin , The study produced a number of results, the most important of which is the presence of Indonesian words of Qur'anic origin from the Qur’an translated into the Indonesian language (al-quran dan terjemahanya) from Surat Al-Fatihah to Surat Al-Nisaa and reached 102 and each language skill have one game.